Does local expenditure composition matter? Brazilian HDI and regional living conditions standards - Basilia Aguirre (European Regional Science Association (ERSA), 2004)
The decentralization process in Brazilian fiscal federalism was legally launched in 1988, when the new federal constitution passed. A considerable part of main public services competencies were assigned to local governments, which are supposed to perform these tasks relying on the financial and technical support from the federation. A large share of the national tax revenues was granted to these jurisdictions, directly or by means of transferences. The higher level of local revenues were not initially translated, however, into better standards of public services, due to a lack of coordination between states and federal government, in addition to technical and administrative local level deficiencies. Over the 1990's the institutional framework underlying Brazilian intergovernmental relations experienced important changes that seek to strength vertical coordination between municipalities and the state/national governments. A variety of new rules were gradually introduced. These rules intended mainly to establish the specific role of each government level for each kind of public service. By 2000 a whole new institutional environment were built. Health care and education programs were the main targets of these changes and it was in these areas that institutionalization of intergovernmental relations went further. Grants on these areas were constitutionally established by constitutional amendments. And, enforcement rules adopted. The aim was to guarantee better public services quality and access to public services. From one theoretical perspective these changes should improve public services by introducing new monitoring mechanisms. From another these changes limit local governments autonomy and hinder local governments capacity to develop policies suitable to local conditions. The arguments in favor of each position are not conclusive and the dilemma is long known in fiscal federalism literature. The question to be addressed by this paper concerns the relation between the centralization trend of Brazilian fiscal federalism structure as represented by the changes pointed above and the potential for diminishing regional disparities. The hypothesis to be tested is that the greater control by federation over the delivery of local public services may improve public services quality as a whole but does not necessarily favours the convergence on living conditions between regions. To do that it will be identified local expenditure patterns in 1990 and 1999 with special emphasis in health and education and related the expenditure shifts to the municipalities 2000 UNO's Human Development Index. Using municipality data for all Brazilian states it will be possible to evaluate first whether different expenditure patterns are related to the improvement on Brazilian Human Development Index for the year 2000, what will indicate that changes in fiscal federalism structure did not limited local governments to follow proper public services policies. Second it will be possible to assess if changes in fiscal federalism rules also contributed to reduce regional disparities in public service delivery as evidenced by HDI results in comparison to 1991.
Keywords: 330